Good Corporate Governance Mechanisms and Financial Performance in Controlling Financial Distress - Yuli Soesetio (ADPEBI International Journal of Business and Social Science, 2023)
Purpose – This study aims to investigate the impact of corporate governance mechanisms on financial distress in firms listed on the Indonesia Stock Exchange (IDX). Methodology/approach – This study uses secondary data from the financial statements of firms, between 2014 and 2019. The number of samples that met the established criteria was 341 firms unbalanced panel, which were further analyzed using logistic regression and sub-group logistic regression analysis. Findings – This study concludes that corporate governance mechanisms (independent commissioners and board size of commissioners), has a mixed impact on financial distress. The larger of board commissioners, the better the company's financial condition, while the proportion of independent commissioners has no significant effect on financial distress. Profitability consistently has a significant effect on financial distress. Ownership i.e. state-owned enterprises (SOE) and non-state-owned enterprises (NSOE) change the direction and impact of liquidity, leverage and board size on financial distress. Novelty/value – Sub-group logistic regression using company ownership variables (i.e. SOE and NSOE) is the novelty of this study. In addition, this study provides insight for companies to always pay attention to profitability avoiding financial distress and and selection of independent commissioners who have relevant experience and background in managing the company.